Survey of the anthropophilic phlebotomine sand flies (Diptera: Psychodidae) of the Serranía de La Macarena, Colombia - BEJARANO, EDUAR ELÍAS; DUQUE, PATRICIA; VÉLEZ, IVÁN DARÍO (Revista Colombiana de Entomología, 2006)
A preliminary survey of the anthropophilic sand fly fauna of the Serranía de La Macarena, Colombia, is presented. Although leishmaniasis is endemic in the region, the vectors of the disease are yet unknown. Insects were collected in July and December using a mouth aspirator while they tried to bite humans between 18:00 and 22:00 hours. Ten species of Lutzomyia sand flies were identified from 89 female specimens collected: L. ayrozai, L. davisi, L. hirsuta hirsuta, L. carrerai carrerai, L. lichyi, L. amazonensis, L. sp. series squamiventris, L. yuilli, L. shawi, and L. sp. series townsendi. The subgenus Psychodopygus was most abundant, with six species that comprised 79.8% of all sand flies collected, followed by Nyssomyia with two species that constituted 16.9% of total captures. The verrucarum group and the subgenus Lutzomyia were each represented by one species. Finally, the epidemiological background of the species encountered are briefly reviewed.